Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1203/pdr.0b013e31802d8a69
|View full text |Cite
|
Sign up to set email alerts
|

Urine Glucose Screening Program at Schools in Japan to Detect Children with Diabetes and Its Outcome-Incidence and Clinical Characteristics of Childhood Type 2 Diabetes in Japan

Abstract: Rev i ew o f P ri m a ry P r eve n t i o n o fTy p e 2 D i a b ete s i n We s te rn Au s t r a l i a E xe c u t i ve S u m m a ry R E V I E W O F P R I M A RY P R E V E N T I O N O F T Y P E 2 D I A B E T E S I N W E S T E R N A U S T R A L I R E V I E W O F P R I M A RY P R E V E

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
95
3
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(102 citation statements)
references
References 25 publications
2
95
3
2
Order By: Relevance
“…Although MetS occurs less often in children, several studies have established a prevalence of MetS in approximately 3.0%-4.0% of children and adolescents [7][8][9] . These phenomena have been reported in Japanese children [10][11][12] . Furthermore, in previous cross-sectional studies, the risk for MetS has been reported to be associated with fatness and aerobic fitness in European 13) , American 14) , Canadian 15) , Australian 16) , and Asian children [17][18][19] .…”
Section: Introductionsupporting
confidence: 61%
“…Although MetS occurs less often in children, several studies have established a prevalence of MetS in approximately 3.0%-4.0% of children and adolescents [7][8][9] . These phenomena have been reported in Japanese children [10][11][12] . Furthermore, in previous cross-sectional studies, the risk for MetS has been reported to be associated with fatness and aerobic fitness in European 13) , American 14) , Canadian 15) , Australian 16) , and Asian children [17][18][19] .…”
Section: Introductionsupporting
confidence: 61%
“…In Japan, a diabetes screening system based on urine glucose testing has been established at schools [11]. In addition, blood examinations for the screening of metabolic abnormalities, such as high glycosylated hemoglobin (HbA1c) level and hypercholesterolemia, have been performed for children in our region who gave consent for these tests.…”
Section: Methodsmentioning
confidence: 99%
“…In Japan, we have a nation-wide diabetes screening system that are targeted at school children and have found a significant number of newly-diagnosed patients with diabetes in this age group [11]. About 30% of patients with childhood-onset type 2 diabetes are nonobese and have a rather rich family history of this disease, which suggests the involvement of genetic factors for diabetes development [12].…”
mentioning
confidence: 99%
“…6. The cost effectiveness of the program should be confirmed periodically in order to maintain enthusiasm for the program the benefits that were realized by the early detection of childhood type 2 diabetes in Japanese children (6).…”
Section: Japanmentioning
confidence: 99%
“…The primary basis for this controversy is the uncertainty as to whether early detection of renal disorders in childhood will lead to effective interventions and reduction in the number of individuals who develop end-stage renal disease (ESRD). There appears to be a clear consensus among Japanese, Taiwanese, and Korean investigators that the screening programs currently in place in these counties have led to early detection and effective intervention (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). However, this opinion is not shared by many investigators elsewhere.…”
mentioning
confidence: 99%